A One‐Pot Route to Faceted FePt‐Fe3O4 Dumbbells: Probing Morphology–Catalytic Activity Effects in O2 Reduction Catalysis. (26th April 2020) - Jenkinson, Kellie J.; Wagner, Andreas; Kornienko, Nikolay; Reisner, Erwin; Wheatley, Andrew E. H.
Abstract: The design and synthesis of faceted nanoparticles with a controlled composition is of enormous importance to modern catalyst engineering. Faceted FePt‐Fe3 O4 dumbbell nanoparticles are prepared by a simple, one‐pot technique that avoids the need for expensive additives or preformed seeds. The faceted product consists of an FePt octopod and a cubic Fe3 O4 lobe, of mean diameter 13.6 and 14.9 nm, respectively. The mass normalized activity for electrocatalytic oxygen reduction shows that this new structure types outperforms related catalysts in alkaline media. This work illustrates the power of morphology control and tailoring crystal facet abundance at the nanoparticle surface for enhancing catalytic performance. Abstract : Finicking with facets. A simple, one‐pot method yields nanoparticles with controlled composition and faceting; FePt‐Fe3 O4 dumbbell nanoparticles no longer need expensive additives or preformed seeds to form. In electrocatalytic oxygen reduction, this new structure‐type outperforms related catalysts in alkaline media, highlighting the power of controlling morphology and surface crystallography.